2004
DOI: 10.1128/aac.48.9.3491-3497.2004
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin-Resistant Invasive Streptococcus pneumoniae in the United States: Evidence for Clonal Spread and the Impact of Conjugate Pneumococcal Vaccine

Abstract: The emergence of fluoroquinolone resistance in sterile-site isolates of Streptococcus pneumoniae is documented in this study characterizing all invasive levofloxacin-resistant (MIC, >8 mg/liter) S. pneumoniae isolates (n ‫؍‬ 50) obtained from the Centers for Disease Control and Prevention Active Bacterial Core Surveillance from 1998 to 2002. Resistance among all isolates increased from 0.1% in 1998 to 0.6% in 2001 (P ‫؍‬ 0.008) but decreased to 0.4% in 2002, while resistance among vaccine serotypes continued t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
87
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 40 publications
0
87
1
2
Order By: Relevance
“…On the other hand, in S. pneumoniae, even within what appeared to be a clonal lineage, there were multiple events of gain and loss of resistance determinants both by point mutations and by horizontal gene transfer (43). In the extreme case, there may be very little clonal spread of a particular resistance phenotype but rather repeated appearance in multiple lineages, as appears to occur for fluoroquinolone resistance in S. pneumoniae (123,124).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in S. pneumoniae, even within what appeared to be a clonal lineage, there were multiple events of gain and loss of resistance determinants both by point mutations and by horizontal gene transfer (43). In the extreme case, there may be very little clonal spread of a particular resistance phenotype but rather repeated appearance in multiple lineages, as appears to occur for fluoroquinolone resistance in S. pneumoniae (123,124).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of quinolone-resistant S. pneumoniae (QRSP) appears to be more dependent on fluoroquinolone selection of de novo spontaneous point mutations in the quinolone resistance-determining regions (QRDRs) of the topoisomerase genes gyrA and parC than on clonal dissemination (9-13). However, some studies reported occurrences of clonal relatedness among QRSP (11,(14)(15)(16).…”
mentioning
confidence: 99%
“…The emergence of quinolone-resistant S. pneumoniae (QRSP) appears to be more dependent on fluoroquinolone selection of de novo spontaneous point mutations in the quinolone resistance-determining regions (QRDRs) of the topoisomerase genes gyrA and parC than on clonal dissemination (9-13). However, some studies reported occurrences of clonal relatedness among QRSP (11,(14)(15)(16).To investigate the relative fitness of QRSP, we conducted a competition study of a fluoroquinolone-susceptible clinical strain of S. pneumoniae (EF3030) with 2 of its fluoroquinolone-resistant isogenic mutants that had 2 common QRDR point mutation combinations. These 3 strains were analyzed by using an in vitro growth model, an in vivo nasopharyngeal colonization model, and an in vivo pneumonia model.…”
mentioning
confidence: 99%
“…1,2 The rapid increase in resistance among common bacterial pathogens, such as Streptococcus pneumoniae, [3][4][5][6] is widely believed to be fueled by high rates of antibiotic use, much of which is unnecessary. [7][8][9][10][11] Because of the communicability of bacterial pathogens, the consequences of resis-tance have an impact on communities in addition to individual carriers.…”
mentioning
confidence: 99%